Evaluasi Tata Kelola Teknologi Informasi Pada PT Nara Summit Industry Dengan Menggunakan Kerangka Cobit 4.0 - Marlina Marlina (Universitas Bina Sarana Informatika, 2016)
Information technology (IT) has become the backbone and most important elements for companies to survive as well as the opportunity to gain a competitive edge. Likewise with PT Nara Summit Industry , which has a dependency with technology. The basic concept is that the COBIT framework in IT controls based on the determination of the necessary information to support the business objectives and the information generated from the combined application of IT processes and related resources. This study discusses the governance of IT in PT Nara Summit Industry , particularly in the information system by using COBIT as procurement framework by limiting the domain only on Plan and Organize (PO), Acquire and Implement (AI). After the analysis of processes related to PT Nara Summit Industry generally has a level of maturity (Maturity Level) at level 3 (defined processes) where management expectations generally at level 4 (managed). Value Index gained maturity shows the level of maturity in each process. To reach a level of maturity that PT Nara Summit Industry has a strategy to address the existing gaps.Keywords:IT Governance, COBIT, PO and AI